Wire rod and steel wire wire with improved strength and softening resistance, and manufacturing method there of

KR103021348B1Active Publication Date: 2026-09-18POHANG IRON & STEEL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020210079432
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-18
Publication Date
2026-09-18
Estimated Expiration
2041-06-18

Smart Images

  • Figure 112021070573694-PAT00001_ABST
    Figure 112021070573694-PAT00001_ABST
Patent Text Reader

Abstract

A wire rod, steel wire, and a method for manufacturing the same are disclosed, with improved strength and resistance to softening. According to one embodiment of the disclosed wire rod with improved strength and softening resistance, in weight percent, it contains C: 0.8 to 1.1%, Si: 0.1 to 0.3%, Mn: 0.2 to 0.8%, Cr: 0.4 to 1.0%, Mo: 0.5 to 1.0%, and the remainder being Fe and other unavoidable impurities, and has a proeutectoid cementite structure with a maximum thickness of 20 μm or more at the austenite grain boundaries in an area fraction of 10% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a wire rod, a steel wire, and a method for manufacturing the same, with improved strength and softening resistance. More specifically, it relates to a wire rod, a steel wire, and a method for manufacturing the same, which have excellent strength and improved softening resistance by controlling the alloy composition and precipitates. Background Technology

[0002] Typically, pre-stressed concrete (PC) steel strands used for reinforcing the outer walls of liquefied natural gas storage tanks and silos are made of carbon steel with a carbon content of 0.7 wt% or more. Meanwhile, steel wires used for reinforcing storage structures are manufactured using steel wires that have a yield strength of about 1,580 MPa and a tensile strength of about 2,360 MPa.

[0003] Globally, the trend toward increasing product strength continues. This is because higher strength not only enables product lightweighting but also offers significant benefits such as shortened construction periods and reduced manufacturing costs.

[0004] Methods to increase the strength of PC steel wire include raising the initial material strength or improving strength through heat treatment, while from a structural perspective, high strength can be secured by forming fine grains. In other words, the higher the initial material strength, the higher the strength can be secured in the final steel wire; furthermore, the finer the grains, the greater the strength can be secured, and the drawing processability can be significantly improved by suppressing cementite fragmentation during drawing.

[0005] Methods for controlling the initial strength and grain size of the material include adding alloying elements such as C and Cr, and controlling process factors such as the microstructure formed during heat treatment and the conditions of the drawing process.

[0006] However, while adding alloying elements is highly effective for increasing strength, controlling process parameters is considered more effective because changes in heat treatment temperature, holding time, and drawing conditions must be taken into account when varying the alloy content. In particular, increasing the amount of drawing is effective among process parameters. However, since the amount of drawing depends heavily on the properties of the material and requires advanced drawing technology, technological enhancement in this area is required.

[0007] Meanwhile, as the size of large buildings for future cities increases, particularly in the Middle East and Europe, and resistance to fire becomes necessary, there is a growing demand for PC steel strands with excellent high-temperature softening resistance.

[0008] One effective method to improve resistance to softening at high temperatures is to precipitate fine carbonitrides. This is because high-temperature strength can be secured by forming fine carbonitride precipitates at high temperatures through the addition of elements such as Cr, Mo, Nb, and V, thereby pinning dislocations within the ferrite grains.

[0009] Bolts used for fastening existing structures have been developed into fire-resistant bolts by precipitating carbonitride precipitates. However, since the development of fire-resistant PC steel strands through precipitation control is currently insufficient, there is a need to develop steel materials with novel alloy compositions. Prior art literature

[0010] Korean Published Patent Application No. 10-2011-0014853 (Date of publication: February 14, 2011) The problem to be solved

[0011] To solve the aforementioned problems, the present invention aims to provide a wire rod, a steel wire, and a method for manufacturing the same, which secure high yield strength and simultaneously improve softening resistance by optimizing the compositional ranges of C, Cr, and Mo and the manufacturing process to control the microstructure and precipitates. means of solving the problem

[0012] The wire rod according to the present invention, which has improved strength and softening resistance to achieve the above-mentioned purpose, comprises, in weight%, C: 0.8 to 1.1%, Si: 0.1 to 0.3%, Mn: 0.2 to 0.8%, Cr: 0.4 to 1.0%, Mo: 0.5 to 1.0%, and the remainder being Fe and other unavoidable impurities, and may have a proeutectoid cementite structure with a maximum thickness of 20 μm or more at the austenite grain boundaries in an area fraction of 10% or less.

[0013] Here, when the diameter of the wire is denoted as D, the maximum carbon content (C) in the region extending from the center of the cross-section perpendicular to the longitudinal direction to the surface of the wire is max The ratio of the average carbon content (C0) to the ) can satisfy the following equation (1).

[0014] Formula (1): C max / C0≤1.25

[0015] Here, in the region where the carbon content of the surface layer of the wire exceeds 0.90 weight%, the bainite structure containing carbides with an average particle size of 1 μm or more may have an area fraction of 90% or more.

[0016] Here, the wire may have a yield strength of 1000 MPa or more.

[0017] Here, the above wire may have an elongation of 12% or more.

[0018] In addition, a method for manufacturing a wire rod with improved strength and softening resistance according to the present invention for achieving the above-mentioned purpose comprises the steps of: maintaining a billet containing, in weight percent, C: 0.8 to 1.1%, Si: 0.1 to 0.3%, Mn: 0.2 to 0.8%, Cr: 0.4 to 1.0%, Mo: 0.5 to 1.0%, and the remainder being Fe and other unavoidable impurities, in a heating furnace at 1000 to 1200°C for 90 to 120 minutes; rolling the billet to manufacture a wire rod; coiling the manufactured wire rod at 900 to 980°C; and first cooling the coiled wire rod from the coiling temperature to 500°C at a cooling rate of 10 to 15°C / s. and a second cooling step of cooling the cooled wire from 500℃ to 300℃ at a cooling rate of 0.1℃ / s or less; is included.

[0019] Here, the rolling may include a step of finishing rolling at 1000 to 1200℃.

[0020] In addition, the steel wire with improved strength and softening resistance according to the present invention for achieving the above-mentioned purpose comprises, in weight percent, C: 0.8 to 1.1%, Si: 0.1 to 0.3%, Mn: 0.2 to 0.8%, Cr: 0.4 to 1.0%, Mo: 0.5 to 1.0%, and the remainder being Fe and other unavoidable impurities, and when quenched after holding at 600°C for 30 minutes, a cross-section of 500 nm perpendicular to the longitudinal direction of the wire rod 2 In the region, the number of MC carbides (where M is Cr or Mo) can be 10 or more.

[0021] Here, the above steel wire may have a yield strength of 780 MPa or more after being held at 600°C for 30 minutes.

[0022] Here, the above steel wire may have a yield strength ratio to tensile strength of 0.35 or higher after being held at 600°C for 30 minutes.

[0023] Here, the steel wire may have a yield strength of 2200 MPa or more.

[0024] Here, the above steel wire may have 12 or more twists at which delamination does not occur, based on 100D.

[0025] Here, the above steel wire may have two or fewer broken wires per ton during drawing.

[0026] In addition, the method for manufacturing a steel wire with improved strength and softening resistance according to the present invention for achieving the above-mentioned purpose comprises the step of drawing the wire rod. Effects of the invention

[0027] According to one aspect of the present invention, by optimizing the compositional range of C, Cr, and Mo and the manufacturing process to control the microstructure and precipitates, it is possible to provide a wire rod, a steel wire, and a method for manufacturing the same that secure high yield strength while simultaneously improving softening resistance. Brief explanation of the drawing

[0028] Figure 1 is a graph of the continuous cooling transformation (CCT) of Example 1 calculated using the J-Mat commercial program. Figure 2 is an equilibrium phase diagram of Example 1 calculated using the Thermo-Cale program. Figure 3 is a graph showing the change in yield strength according to temperature when Example 1 and Comparative Example 8 were quenched after being maintained at their respective temperatures for 30 minutes. Specific details for implementing the invention

[0029] Preferred embodiments of the present invention are described below. However, embodiments of the present invention may be modified in various other forms, and the technical concept of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those with average knowledge in the relevant technical field.

[0030] The terms used in this application are used merely to describe specific examples. For this reason, singular expressions include plural expressions unless the context clearly requires them to be singular. Additionally, it should be noted that terms such as “comprising” or “comprising” used in this application are used to clearly indicate the presence of features, steps, functions, components, or combinations thereof described in the specification, and are not used to preliminarily exclude the existence of other features, steps, functions, components, or combinations thereof.

[0031] Meanwhile, unless otherwise defined, all terms used in this specification shall be understood to have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Accordingly, unless explicitly defined in this specification, specific terms should not be interpreted in an overly ideal or formal sense. For instance, singular expressions in this specification include plural expressions unless the context clearly indicates an exception.

[0032] Additionally, terms such as "about," "substantially," etc., in this specification are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the said sense, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosed content in which precise or absolute values ​​are mentioned to aid in understanding the invention.

[0033] A wire rod with improved strength and softening resistance according to one embodiment of the present invention comprises, in weight%, C: 0.8 to 1.1%, Si: 0.1 to 0.3%, Mn: 0.2 to 0.8%, Cr: 0.4 to 1.0%, Mo: 0.5 to 1.0%, and the remainder being Fe and other unavoidable impurities.

[0034] Here, the wire rod with improved strength and softening resistance may further contain, in weight%, N: 0.01% or less, P: 0.035% or less, S: 0.035% or less, and Al: 0.02 to 0.05%.

[0035] The reasons for limiting the compositional range of each alloying element are explained below. Unless otherwise noted, units are weight percent.

[0036] The content of C is 0.8 to 1.1%.

[0037] Carbon (C) increases the fraction of cementite constituting pearlite and reduces the interlayer spacing of pearlite. As a solid solution strengthening element that increases strength by approximately 80 MPa when 0.1 wt% is added, it can be added at a rate of 0.8% or more to ensure the strength of the material. However, if the content is excessive, it causes the formation of center segregation, which leads to wire breakage during drawing processing. Considering this, the upper limit of the C content may be limited to 1.1%.

[0038] The Si content is 0.1 to 0.3%.

[0039] Silicon (Si) is a ferrite-hardening element and can be added in an amount of 0.1% or more to remove oxygen from the molten steel and improve strength. However, if the content is excessive, there is a problem where scale peelability decreases due to the formation of Fe2sSiO4, which has excellent bonding strength with the base material. Considering this, the upper limit of the Si content can be limited to 0.3%.

[0040] The Mn content is 0.2 to 0.8%.

[0041] Manganese (Mn) is an austenite-stabilizing element and can be added in an amount of 0.2% or more to improve hardenability and suppress the formation of proeutectoid cementite at grain boundaries. However, if the content is excessive, it combines with S to form MnS inclusions, and manganese segregation in the center occurs, which increases the risk of wire breakage during drawing. Considering this, the upper limit of the Mn content may be restricted to 0.8%.

[0042] The Cr content is 0.4 to 1.0%.

[0043] Chromium (Cr) can increase the strength of the product by reducing the grain size that hinders the movement of dislocations, such as in bainite and pearlite. Additionally, as Cr is a major element that forms Cr-based carbides when held at high temperatures, it can be added at a level of 0.4% or more to ensure resistance to softening at temperatures around 600°C. However, if the content is excessive, martensite forms in the central segregation zone, resulting in poor drawing performance and saturating the effects on the target strength and resistance to softening. Considering this, the upper limit of the Cr content may be restricted to 1.0%.

[0044] The Mo content is 0.5 to 1.0%.

[0045] Molybdenum (Mo) is an element that improves the strength of the material through precipitation strengthening effects by forming MoC carbides and enhances the work hardening rate during drawing by pinning dislocations. In addition, Mo, along with Cr, is an element that improves resistance to softening at high temperatures, and can be added in an amount of 0.5% or more to prevent a decrease in yield strength at temperatures around 600°C. However, if the content is excessive, a martensite phase is formed in the cooling zone, making it impossible to secure the bainite structure targeted in this invention. Furthermore, Mo is an expensive element, and an excessive content raises manufacturing costs, leading to a problem of reduced productivity. Considering this, the upper limit of the Mo content may be limited to 1.0%.

[0046] The content of N is 0.01% or less.

[0047] N (nitrogen) is an element with excellent strength increase through solid solution strengthening. However, if its content is excessive, the bonding of dislocations with N increases aging strength, which leads to inferior ductility of the material and an increase in manufacturing costs. Considering this, the upper limit of the N content can be limited to 0.01%.

[0048] The P content is 0.035% or less.

[0049] Phosphorus is typically difficult to avoid in central segregation zones when the carbon content in steel is high, and it may segregate at grain boundaries or form as FeP at grain boundaries, which causes wire breakage during drawing. Considering this, the upper limit of the P content can be limited to 0.035%.

[0050] The S content is 0.035% or less.

[0051] When S (sulfur) is present in large amounts, it forms MnS inclusions at grain boundaries, which causes a problem of reduced processability. Considering this, the upper limit of the S content can be limited to 0.035%.

[0052] The Al content is 0.02 to 0.05%.

[0053] Al (aluminum) is an element that reacts readily with oxygen, and when the Si content is low, it can be added at a level of 0.02% or more to control inclusions by utilizing it in the deoxidation reaction of steelmaking. However, if the content is excessive, nozzle clogging due to inclusions occurs during continuous casting, and in particular, coarse aluminum inclusions such as Al2O3 are formed, causing wire breakage during drawing. Considering this, the upper limit of the Al content can be limited to 0.05%.

[0054] In addition to the composition mentioned above, the remaining component is iron (Fe). However, since unintended impurities from raw materials or the surrounding environment may inevitably be incorporated during the ordinary manufacturing process, they cannot be excluded. As these impurities are known to any person skilled in the ordinary manufacturing process, all details thereof are not specifically mentioned in this specification.

[0055] In addition, a wire rod according to one embodiment of the present invention may comprise a pearlite structure of 80% or more in area fraction and a bainite structure or martensite structure in remainder. At this time, a proeutectoid cementite structure with a maximum thickness of 20 μm or more at the austenite grain boundaries may comprise 10% or less in area fraction.

[0056] When the area fraction of proeutectoid cementite structure with a maximum thickness of 20㎛ or more at austenite grain boundaries exceeds 10%, cracks are prone to occur during drawing, and drawing workability deteriorates.

[0057] In addition, the wire rod according to one embodiment of the present invention has a maximum carbon content (C) in the region from the center of the cross-section perpendicular to the longitudinal direction to 0.25D in the direction of the wire rod surface. max The ratio of ) and the average carbon content (C0) can satisfy the following equation (1). Here, D represents the diameter.

[0058] Formula (1): C max / C0≤1.25

[0059] Maximum carbon content inside the wire (C max The ratio of ) and the average carbon content (CO) is a factor affecting ~. In the region from the center of the cross-section perpendicular to the longitudinal direction to 0.25D in the direction of the wire surface, the maximum carbon content (C max If the ratio of the average carbon content (CO) to the average carbon content exceeds 1.25, the central C segregation increases, which degrades workability and may cause wire breakage during fresh processing.

[0060] In addition, in a region where the carbon content of the surface layer of the wire rod according to one embodiment of the present invention exceeds 0.90 weight%, the bainite structure containing carbides with an average particle size of 1 μm or more may have an area fraction of 90% or more.

[0061] In the region where the carbon content of the surface layer of the wire exceeds 0.90 weight%, if the bainite structure containing carbides with an average grain size of 1 μm or more is less than 90% in area fraction, a problem of reduced yield strength may occur.

[0062] In addition, the wire according to one embodiment of the present invention may have a yield strength of 1000 MPa or more.

[0063] In addition, the wire according to one embodiment of the present invention may have an elongation of 12% or more.

[0064] Next, a method for manufacturing a wire rod with improved strength and softening resistance according to one embodiment of the present invention will be described.

[0065] A method for manufacturing a wire rod according to one embodiment of the present invention comprises: a step of maintaining a billet containing, in weight%, C: 0.8 to 1.1%, Si: 0.1 to 0.3%, Mn: 0.2 to 0.8%, Cr: 0.4 to 1.0%, Mo: 0.5 to 1.0%, and the remainder being Fe and other unavoidable impurities, in a heating furnace at 1000 to 1200°C for 90 to 120 minutes; a step of manufacturing a wire rod by rolling the billet; a step of coiling the manufactured wire rod at 900 to 980°C; a step of first cooling the coiled wire rod to 500°C at a cooling rate of 10 to 15°C / s; and a step of second cooling the cooled wire rod to 300°C at a cooling rate of 0.1°C / s or less.

[0066] Here, the billet may further contain, in weight%, N: 0.01% or less, P: 0.035% or less, S: 0.035% or less, and Al: 0.02 to 0.05%.

[0067] The reason for limiting the compositional range of each alloying element is as described above, and each manufacturing step is explained in more detail below.

[0068] First, a billet having the compositional components described above is prepared, and then undergoes a heating step to homogenize it into a single austenite phase.

[0069] The above heating step can be performed at a temperature of 1000°C or higher to secure the temperature range for subsequent wire rod rolling, secure the microstructure of the billet as an austenite single phase, and take into account the charging time. However, if the temperature of the above heating step is excessive, surface quality may deteriorate due to scale formation and decarburization, and problems may arise where the heating furnace is overloaded. Taking this into consideration, the upper limit of the above heating temperature may be limited to 1200°C.

[0070] In addition, the heating step may be performed for 90 minutes to secure an austenite phase in the center of the wire and to sufficiently dissolve solid solution strengthening elements to secure strength. However, if the heating time is excessively long, coarse grains may be formed, which may result in a problem where sufficient strength cannot be secured. Considering this, the upper limit of the heating time may be limited to 120 minutes.

[0071] Next, the heated billet can be rolled under normal rolling conditions. That is, a wire rod can be manufactured by performing hot rolling on the heated billet, which consists sequentially of rough rolling, intermediate rough rolling / finish rolling, and finish rolling.

[0072] At this time, the rolling may include a step of finishing rolling at 1000 to 1200°C. Here, it is preferable to control the temperature as the finishing rolling shear temperature. Considering that the temperature of the material is high after finishing rolling before finishing rolling, it is more preferable to control it as the finishing rolling shear entry temperature.

[0073] When the finish rolling temperature is below 1000℃, a large roll load may occur during finish rolling, and as the time available for C to diffuse decreases, the amount of C segregation in the center of the wire rod may increase. As a result, when the finish rolling temperature is below 1000℃, the maximum carbon content (C) relative to the average carbon content (C0) of the material max The ratio can exceed 1.25.

[0074] On the other hand, if the finishing rolling temperature exceeds 1200℃, the processing heat not only accelerates dynamic strain aging of the wire rod during processing but also accelerates static strain aging after processing, which can cause interlayer separation in the wire rod.

[0075] Next, the manufactured wire can be wound at a temperature range of 900 to 980°C.

[0076] At this time, if the winding temperature is less than 900℃, the scale thickness is thin, which is disadvantageous in terms of peelability. On the other hand, if the winding temperature exceeds 980℃, the winding shape is not suitable and excessive scale may form during cooling.

[0077] Meanwhile, the above-mentioned wound wire has a maximum carbon content (C) in the region up to 0.25D from the center of the cross-section perpendicular to the longitudinal direction toward the wire surface. max The ratio of the average carbon content (C0) to the average carbon content (C0) can satisfy the following equation (2). Here, D represents the diameter of the wire.

[0078] Equation (2): 1≤C max / C0≤1.1

[0079] Next, a first cooling step can be performed on the wound wire at a cooling rate of 10 to 15℃ / s from the winding temperature to 500℃.

[0080] The above first cooling step may be cooled to 500°C, which is a temperature below A1, in order to suppress the formation of proeutectoid cementite. At this time, if the cooling rate is less than 10°C / s, the area fraction of the proeutectoid cementite structure with a maximum thickness of 20 μm or more at the austenite grain boundaries exceeds 10%, which may cause wire breakage during wire drawing. If the cooling rate exceeds 15°C / s, a problem arises in which additional costs are incurred for the process.

[0081] Next, a second cooling step can be performed to extremely cool the first cooled wire from 500°C to 300°C.

[0082] If the cooling rate in the second cooling stage exceeds 0.1℃ / s, more than 10% of martensite is formed, which degrades workability and may cause wire breakage during drawing. Considering this, the cooling rate in the second cooling stage may be limited to 0.1℃ / s or less.

[0083] Afterwards, the above wire can be descaled and then drawn to produce steel wire. At this time, the drawing process can be carried out with a total drawing reduction of 87% or more.

[0084] Next, a steel wire with improved strength and softening resistance according to one embodiment of the present invention will be described.

[0085] A steel wire according to one embodiment of the present invention comprises, in weight%, C: 0.8 to 1.1%, Si: 0.1 to 0.3%, Mn: 0.2 to 0.8%, Cr: 0.4 to 1.0%, Mo: 0.5 to 1.0%, and the remainder being Fe and other unavoidable impurities.

[0086] Here, the steel wire with improved strength and softening resistance may further include, in weight%, N: 0.01% or less, P: 0.035% or less, S: 0.035% or less, and Al: 0.02 to 0.05%.

[0087] The reason for limiting the compositional range of each alloying element is as described above.

[0088] In addition, the steel wire according to one embodiment of the present invention, when quenched after being held at 600°C for 30 minutes, has a cross-section of 500 nm perpendicular to the longitudinal direction of the wire. 2 The number of MC carbides in the region can be 10 or more, regardless of their size.

[0089] Here, M represents Cr or Mo, and the number of carbides refers to the number of MC carbides measured regardless of size, such as average particle size, maximum diameter, etc. The above quenching can be performed by conventional methods such as water cooling, oil cooling, air cooling, or furnace cooling.

[0090] 500nm of the cross-section perpendicular to the longitudinal direction of the wire 2 In the region, if the number of MC carbides is less than 10, resistance to softening at high temperatures cannot be secured. On the other hand, if the number of MC carbides is 10 or more, the decrease in yield strength at high temperatures can be suppressed.

[0091] According to one embodiment of the present invention, as MC carbides are formed, the steel wire can suppress the decrease in yield strength even after being held at 600°C for 30 minutes, thereby securing a yield strength of 780 MPa or higher.

[0092] In addition, the steel wire according to one embodiment of the present invention may have a yield strength ratio of 0.35 or higher as a result of suppressing the decrease in yield strength even after being maintained at 600°C for 30 minutes.

[0093] In addition, the steel wire according to one embodiment of the present invention may have a yield strength of 2200 MPa or more.

[0094] In addition, the steel wire according to one embodiment of the present invention may have 12 or more twists in which delamination does not occur, based on 100D.

[0095] In addition, the steel wire according to one embodiment of the present invention may have two or fewer wire breakage times per ton during drawing.

[0096] A wire rod according to one embodiment of the present invention can be used to manufacture high-strength PC steel wire, steel strand, PC steel strand, etc. In addition, a steel wire according to one embodiment of the present invention can be manufactured using current heat treatment facilities without undergoing LP heat treatment. Furthermore, by ensuring strength while preventing a decrease in yield strength at high temperatures, a fire resistance effect can be secured.

[0097] The present invention will be explained in more detail below through examples. However, the description of these examples is merely for illustrating the implementation of the present invention and does not limit the present invention. This is because the scope of the rights of the present invention is determined by the matters described in the patent claims and matters reasonably inferred therefrom.

[0098] {Example}

[0099] Steel satisfying the various alloy compositions shown in Table 1 below is steeled in a furnace, and then cast under normal conditions to a size of 160*160mm 2 A continuous casting billet was manufactured. Afterwards, the manufactured billet was maintained at a furnace temperature of 1,150°C for 95 minutes for the purpose of securing the austenite phase and strength.

[0100] weight% C Si Mn Cr Mo Example 1 0.98 0.2 0.6 0.6 0.6 Example 2 1.08 0.2 0.6 0.6 0.6 Example 3 0.98 0.2 0.6 0.9 0.6 Example 4 0.98 0.2 0.6 0.6 0.9 Comparative Example 1 0.98 0.2 0.6 0.6 0.6 Comparative Example 2 0.98 0.2 0.6 0.6 0.6 Comparative Example 3 0.98 0.2 0.6 0.6 0.6 Comparative Example 4 0.98 0.2 0.6 0.6 0.6 Comparative Example 5 1.12 0.2 0.6 0.6 0.6 Comparative Example 6 0.98 0.2 0.6 1.2 0.6 Comparative Example 7 0.98 0.2 0.6 0.6 1.1 Comparative Example 8 0.98 0.2 0.6 0.2 0.2

[0102] Next, wire rods were manufactured by rolling according to the finish rolling temperature conditions in Table 2 below. The finish rolling temperature in Table 2 below refers to the temperature at the shear entry side before finish rolling after finishing rolling.

[0103] Subsequently, the manufactured wire rod was wound, and the wound wire rod was subjected to a first cooling process to 500°C, followed by a second cooling process from 500°C to 300°C. Table 2 below shows the temperature of the winding process and the maximum carbon content (C) relative to the average carbon content (CO) of the wound wire rod. max The ratio of ), the first cooling process, and the cooling rate of the second cooling process were shown.

[0104] Finish rolling temperature (°C) Winding temperature (°C) Cooling rate up to 500℃ (℃ / s) Cooling rate up to 300℃ (℃ / s) Example 1 1,050 950 14 0.1 Example 2 1,050 950 14 0.1 Example 3 1,050 950 14 0.1 Example 4 1,050 950 14 0.1 Comparative Example 1 950 950 14 0.1 Comparative Example 2 900 950 14 0.1 Comparative Example 3 1,050 950 4 0.1 Comparative Example 4 1,050 950 14 5 Comparative Example 5 1,050 950 14 0.1 Comparative Example 6 1,050 950 14 0.1 Comparative Example 7 1,050 950 14 0.1 Comparative Example 8 1,050 950 14 0.1

[0106] After the cooling process, the fraction of primary cementite in the wire rod, C max / CO, bainite fraction, yield strength (YS), and elongation were measured and are shown in Table 3 below.

[0107] The proeutectoid cementite fraction in Table 3 below refers to the area fraction of the proeutectoid cementite structure with a maximum thickness of 20 μm or more at the austenite grain boundaries. The maximum thickness of the cementite structure was calculated from the following equation (3) after measuring the pearlite laminar spacing in a cross-section perpendicular to the longitudinal direction of the wire using a scanning electron microscope (SEM) with model name S-3700N.

[0108] Equation (3): t c ={S0*0.15(wt%C)} / V p

[0109] In the above equation (3), t c ε is the maximum thickness of the cementite structure, S0 is the lamellar spacing, V p represents the measured pearlite fraction, and wt%C represents the carbon content of the specimen.

[0110] C in Table 3 below max / C0 is the maximum carbon content (C) relative to the average carbon content (C0). max It means the ratio of ).

[0111] The bainite fraction in Table 3 below refers to the area fraction of bainite structure containing carbides with an average grain size of 1 μm or more in the region where the carbon content of the surface layer of the wire rod exceeds 0.90 wt%.

[0112] For the bainite fraction, the region where the carbon content exceeded 0.90 wt% was first measured. Subsequently, the area of ​​1 mm in that region 2 The area fraction of the bainite structure was measured using a scanning electron microscope at eight random locations, and the average value was calculated.

[0113] Wire rod, nitrate, cementite fraction (%) Seonjae C max / C0 Wire Bainite Fraction (%) Wire yield strength (MPa) Wire elongation (%) Example 1 9 1.17 91 1,080 14 Example 2 9 1.21 91 1,170 13 Example 3 10 1.22 90 1,140 13 Example 4 10 1.24 92 1,180 12 Comparative Example 1 9 1.51 89 1,014 10 Comparative Example 2 8 1.86 88 970 7 Comparative Example 3 16 1.17 89 1,069 4 Comparative Example 4 9 1.18 78 780 4 Comparative Example 5 9 1.38 87 1,200 10 Comparative Example 6 9 1.17 86 1,190 9 Comparative Example 7 10 1.24 84 1,240 4 Comparative Example 8 8 1.15 92 920 18

[0115] Referring to Table 1 above, based on the component composition of Example 1, C was added in Example 2. Meanwhile, based on the component composition of Example 1, Cr was added in Example 3, and Mo was added in Example 4.

[0116] Referring to Tables 2 and 3 above, Examples 1 to 4 satisfied the alloy composition and manufacturing process conditions controlled in the present invention, resulting in a wire rod proeutectoid cementite structure of 10% or less and a wire rod bainite structure fraction of 90% or more.

[0117] In addition, as a result of performing the finish rolling of Examples 1 to 4 at a temperature of 1000 to 1200°C, the time for C to diffuse increased. Accordingly, in Examples 1 to 4, the amount of C segregation in the center of the wire rod was reduced, and C max / C0 value satisfied 1.25 or less.

[0118] In addition, Examples 1 to 4 were able to secure a wire yield strength of 1000 MPa or more and an elongation of 12% or more.

[0119] In contrast, Comparative Example 1 was performed at 950°C, where the finishing rolling temperature was less than 1000°C, resulting in C maxThe / C0 value was 1.51, which exceeded 1.25. In addition, Comparative Example 1 had a bainite structure formed in less than 90% and an elongation of 10%, which was inferior.

[0120] Comparative Example 2 is the result of a rolling process performed at 900℃, where the finishing rolling temperature is less than 1000℃, C max The / C0 value increased significantly to 1.86. In addition, Comparative Example 2 had a bainie structure of less than 90%, and the yield strength and elongation were inferior.

[0121] Comparative Example 3 was cooled from a coiling temperature to 500°C at a cooling rate of 4°C / s, which is less than 10°C / s. As a result, the fraction of proeutectoid cementite structure with a thickness of 20 or more at the grain boundaries increased significantly from 10% to 16%. Accordingly, Comparative Example 3 had inferior processability with an elongation of 4%, and bainite structure was formed at less than 90%.

[0122] Comparative Example 4 was cooled from 500°C to 300°C at a cooling rate of 5°C / s exceeding 0.1°C / s, and as a result, the fraction of the bainite structure was significantly reduced to 78%, making it unsuitable for production as a final product.

[0123] In Comparative Example 5, as C was added in excess of 1.1%, the value of Cmax / C0 increased to 1.38. Additionally, in Comparative Example 5, the bainite structure was formed in less than 90%, and the elongation was inferior at 10%.

[0124] Comparative Example 6 had 1.2% Cr added, which exceeded 1.0%, resulting in inferior processability with an elongation of 9% and a bainite structure formed at 86%, which was less than 90%.

[0125] Comparative Example 7 had poor processability with an elongation of 4% as Mo was added at 1.1%, which exceeded 1.0%, and a bainite structure of less than 90%, with 84%.

[0126] Comparative Example 8 had 0.2% of Cr added, which is less than 0.4%, and 0.2% of Mo added, which is less than 0.5%. As a result, Comparative Example 8 had a problem where the yield strength was significantly reduced to 920 MPa, which is less than 1000 MPa.

[0127] Next, the manufactured wire rod was partially descaled on the surface using a mechanical peeling method, and then wire drawing was performed with a total wire reduction of 87%.

[0128] The total fresh reduction amount was calculated using the following equation (4).

[0129] Equation (4): Total fresh reduction amount (%) = 100*[1-(diameter after freshing / diameter before freshing) 2 ]

[0130] Table 4 below shows the results after measuring the yield strength, twisting cycles, number of broken wires per ton, and whether the number of MC carbides was 10 or more of the steel wire manufactured above.

[0131] In Table 4 below, the evaluation of the torsional characteristics of the steel wire was performed by applying a load of tensile strength * cross-sectional area * 0.008 to the manufactured steel wire using a general-purpose torsional testing machine (back load: fracture stress x 0.2) and measuring the number of twists based on a torsional length of 100 * D (D: diameter of the steel wire).

[0132] In Table 4 below, the number of MC carbides (M is Cr or Mo) refers to the number of MC carbides measured regardless of size. The number of MC carbides is based on an area of ​​500 nm on the surface layer of the wire rod. 2 Eight random locations were measured using a scanning electron microscope, and the average value was calculated. In Table 4 below, '○' indicates cases where the number of MC carbides is 10 or more, and 'X' indicates cases where the number of MC carbides is less than 10.

[0134] Total fresh discount amount (%) Wire yield strength (MPa) Steel wire twisting (time) Processing wire (number of times / ton) Whether MC carbides are 10 or more Example 1 87 2,210 16 0.4 ○ Example 2 87 2,300 15 0.5 ○ Example 3 87 2,280 14 0.7 ○ Example 4 87 2,290 12 0.9 ○ Comparative Example 1 87 1,896 11 2.5 ○ Comparative Example 2 87 1,859 11 3.8 ○ Comparative Example 3 87 2,150 8 4.2 ○ Comparative Example 4 87 1,805 1 20.1 ○ Comparative Example 5 87 2,300 4 19.2 ○ Comparative Example 6 87 2,310 6 17.4 ○ Comparative Example 7 87 2,340 2 22.7 ○ Comparative Example 8 87 2,080 18 0.1 X

[0135] Examples 1 to 4 had excellent yield strength of 2000 MPa or higher and satisfied the condition of having 10 or more MC carbides. In addition, Examples 1 to 4 had 12 or more twists without delamination and satisfied the condition of 2 or fewer wire breakage per ton during drawing, thus having excellent processability.

[0136] In contrast, Comparative Examples 1 and 2 had a yield strength of less than 2000 MPa, a twisting frequency of less than 12, and a processing wire breakage frequency of more than 2.

[0137] Comparative Example 3 secured a yield strength of 2000 MPa or more, but had inferior processability with a twisting frequency of 8 times, which was less than 12 times, and a processing failure frequency of 4.2 times, which exceeded 2 times.

[0138] Comparative Example 4 was inferior with a yield strength of 1805 MPa, which is less than 2000 MPa, and had a twisting frequency of 1 time and a processing wire breakage frequency of 20.1 times, resulting in significantly reduced processability and a problem where it could not be produced as a final product.

[0139] Comparative Examples 5 to 7 secured a yield strength of 2000 MPa or more, but the number of twists was less than 12, and the number of wire breaks during processing exceeded 2, resulting in poor processability.

[0140] Figure 3 is a graph showing the change in yield strength according to temperature when Example 1 and Comparative Example 8 were quenched after being maintained at their respective temperatures for 30 minutes.

[0141] Referring to FIG. 3, when quenched after being maintained at a temperature of 0 to 500°C for 30 minutes, the reduction in yield strength of Example 2 and Comparative Example 8 did not show a significant difference. However, since Comparative Example 8 had fewer than 10 MC carbides formed, the yield strength of Comparative Example 8 decreased significantly compared to Example 2 at a temperature of 600°C or higher.

[0142] In addition, in the case of Comparative Example 8, when quenched after being held at 600°C for 30 minutes, the ratio of yield strength to tensile strength was 0.21. On the other hand, in the case of Example 1, when quenched after being held at 600°C for 30 minutes, the ratio of yield strength to tensile strength was 0.35, which was 166% of the value of Comparative Example 8.

[0143] According to the disclosed embodiments, it can be seen that by optimizing the alloy composition and manufacturing process, excellent yield strength and elongation can be secured, while at the same time, the decrease in yield strength at high temperatures of 600°C can be suppressed.

Claims

Claim 1 In weight%, it contains C: 0.8 to 1.1%, Si: 0.1 to 0.3%, Mn: 0.2 to 0.8%, Cr: 0.4 to 1.0%, Mo: 0.5 to 1.0%, and the remainder being Fe and other unavoidable impurities, and the area fraction of a proeutectoid cementite structure with a maximum thickness of 20 μm or more at the austenite grain boundaries is 10% or less, and when the diameter of the wire rod is D, in the region from the center of the cross-section perpendicular to the longitudinal direction to the wire rod surface up to 0.25 D, the maximum carbon content (C max A wire rod with improved strength and softening resistance, wherein the ratio of the average content of carbon (C0) satisfies the following formula (1), and in the region where the carbon content of the surface layer of the wire rod exceeds 0.90 weight%, the bainite structure containing carbides with an average grain size of 1 μm or more has an area fraction of 90% or more. (1): C max / C0≤1.25 Claim 2 delete Claim 3 delete Claim 4 In claim 1, a wire rod with improved strength and softening resistance, having a yield strength of 1000 MPa or more. Claim 5 In claim 1, a wire rod with improved strength and softening resistance having an elongation of 12% or more. Claim 6 A step of maintaining a billet comprising, in weight percent, C: 0.8 to 1.1%, Si: 0.1 to 0.3%, Mn: 0.2 to 0.8%, Cr: 0.4 to 1.0%, Mo: 0.5 to 1.0%, and the remainder being Fe and other unavoidable impurities, in a heating furnace at 1000 to 1200°C for 90 to 120 minutes; a step of finishing rolling the billet at 1000 to 1200°C to produce a wire rod; a step of coiling the produced wire rod at 900 to 980°C; and a step of first cooling the coiled wire rod from the coiling temperature to 500°C at a cooling rate of 10 to 15°C / s. A method for manufacturing a wire rod with improved strength and softening resistance, comprising: a second cooling step of cooling the cooled wire rod from 500℃ to 300℃ at a cooling rate of 0.1℃ / s or less. Claim 7 delete Claim 8 In weight percent, it comprises C: 0.8 to 1.1%, Si: 0.1 to 0.3%, Mn: 0.2 to 0.8%, Cr: 0.4 to 1.0%, Mo: 0.5 to 1.0%, and the remainder being Fe and other unavoidable impurities, and a 500 nm cross-section perpendicular to the longitudinal direction of the steel wire. 2 A steel wire with improved strength and softening resistance, having 10 or more MC carbides (where M is Cr or Mo) in the region, a yield strength of 2200 MPa or more, and 12 or more twists at which delamination does not occur based on 100D. Claim 9 In claim 8, a steel wire with improved strength and softening resistance, having a yield strength of 780 MPa or more after holding at 600°C for 30 minutes. Claim 10 In claim 8, a steel wire with improved strength and softening resistance, having a yield strength to tensile strength ratio of 0.35 or higher after being held at 600℃ for 30 minutes. Claim 11 delete Claim 12 delete Claim 13 A method for manufacturing a steel wire with improved strength and softening resistance, comprising the step of drawing a wire rod with improved strength and softening resistance according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method for producing high-ductility direct patenting wire rod

    JP2008007856A

  • Steel wire rod excellent in mechanical descalabilityand manufacturing method thereof

    KR1020030082997A

  • Wire rod and its manufacturing method

    KR1020190073456A